Podrobnosti . Podrobnosti . Details . Подробности - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Predictions concerning the Federal Assembly; interview with Gennadii Burbulis, State Duma representative for "Vybor Rossii" ("Russia's Choice"). Featured in the program: Gaidar, Egor Timurovich (First Deputy Prime Minister of the Russian Federation); Burbulis, Gennadii Eduardovich (Deputy of the State Duma) Contributors: Svanidze, Nikolai (Anchor) Прогнозы работы Федерального Собрания; интервью с Геннадием Бурбулисом, представителем думской фракции "Выбор России.". В программе участвуют: Гайдар, Егор Тимурович (Первый заместитель председателя Правительства Российской Федерации); Бурбулис, Геннадий Эдуардович (Депутат Государственной Думы) Создатели: Сванидзе, Николай (Ведущий/Ведущая)